2000
DOI: 10.1183/09031936.00.16586100
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with fish oil rich in omega-3 polyunsaturated fatty acids in children with bronchial asthma

Abstract: Omega-3 polyunsaturated fatty acids have anti-inflammatory effects in vitro, and high dietary levels are associated with a lower incidence of inflammatory diseases. However, only limited effects have been demonstrated in asthma. The effects of dietary supplementation with fish oil for 10 months in 29 children with bronchial asthma was investigated in a randomized controlled fashion. In order to minimize the effects of environmental inhaled allergens and diet, this study was performed in a long-term treatment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
3
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(164 citation statements)
references
References 17 publications
5
151
3
5
Order By: Relevance
“…It is discussed whether an intervention at an earlier age, before allergic immune responses are established, might provide clearer health benefits (Calder, 2003). With respect to asthma, intervention studies with n-3 PUFA seem to support a protective effect of n-3 PUFA on the onset of allergic diseases (asthma) in childhood (Nagakura et al, 2000;Mihrshahi et al, 2003). In a Norwegian study, early introduction of fish in the diet was inversely associated with the risk of allergic rhinitis (Nafstad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is discussed whether an intervention at an earlier age, before allergic immune responses are established, might provide clearer health benefits (Calder, 2003). With respect to asthma, intervention studies with n-3 PUFA seem to support a protective effect of n-3 PUFA on the onset of allergic diseases (asthma) in childhood (Nagakura et al, 2000;Mihrshahi et al, 2003). In a Norwegian study, early introduction of fish in the diet was inversely associated with the risk of allergic rhinitis (Nafstad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies (121,123) have reported AHR in terms of the provocation dose of histamine required to produce a 35 % fall in specific conductance and showed no effect of n-3 fatty acid supplementation on AHR. In children, Nagakura et al (124) reported AHR as the provocative concentration of acetylcholine causing a 20 % fall in FEV 1 for each subject and saw a reduction in acetylcholine responsiveness in the n-3 fatty acid group but not in the control group (124) . Schubert et al (119) reported a reduction in AHR after an allergen challenge with n-3 fatty acid supplementation; however, this change failed to reach significance (119) .…”
Section: Evidence From N-3 Intervention Trials In Asthmamentioning
confidence: 99%
“…[67][68][69][70] Increases in dietary and inflammatory cell n-3:n-6 PUFA ratio have been associated with improvements in asthma outcomes. [71][72][73][74][75] Interestingly, a Mediterranean diet higher in n-3 fatty acids and antioxidants appears to protect young children from recurrent wheezing. 76 Obese children on average consume more n-6 dietary PUFAs, have a reduced n-3:n-6 ratio in their diet, 77 and have reduced n-3:n-6 PUFA serum levels compared to similar leans.…”
Section: Dietary Factorsmentioning
confidence: 99%